Cliff edges in the Irish tax-benefit system - Michael Doolan; Claire Keane (The Economic and Social Research Institute (ESRI), 2023)
Trade-offs exist in protecting those on lower incomes and ensuring an adequate incentive to work. If benefit entitlements and other supports are withdrawn sharply as income rises, there may be a financial disincentive to enter employment or to work more. The same is true for tax and social insurance liabilities - if these jump at certain points or increase sharply they may disincentivise employment. This paper examines cliff edges that exist in the Irish tax and welfare system - such as income thresholds for medical cards and Pay-Related Social Insurance (PRSI) contributions - that can mitigate against the generally strong incentives to work faced by the working-age population. Where possible, it considers options for reforms to these cliff edges.
Keywords: 330